Availability of apicoectomy information online. (15th May 2015) - Ritchie, M.; Awal, D.; Eyeson, J.D.
Abstract: Aim: The aim of this study is to ascertain the quality of information available to the public on the Internet regarding the apicoectomy procedure utilising common internet search terms. Materials and methods: The five most widely used UK Internet search engines were utilised, searching for the term 'apicoectomy OR root end surgery'. The first 10 website links brought up on each search engine were then investigated for their contents. The indication for the procedure, details regarding the procedure technique, potential complications and treatment prognosis were all assessed. The topics were evaluated with a scoring system of 0–2 regarding the quality of information contained as compared with the apicoectomy information published on the British Association of Oral Surgeons (BAOS) website. A Flesch Reading Ease Score was also used to assess readability. Results: All 50 websites were easily accessible (100%). Two per cent had any form of accreditation by a healthcare website accreditation organisation. Eighty‐two per cent were targeted at the general public rather than healthcare professionals. Seventy‐two per cent had an unspecified author with no obvious affiliation. Eight per cent contained any form of reference. Generally, the complications and prognosis of the apicoectomy procedure were poorly covered, with the indications and technique scoring higher. Conclusions: The information currently available to patients on the apicoectomy procedure is generally of substandard quality, lacking in terms of content and accreditation. Important facts which are central to the decision‐making process for patients concerning potential complications and long‐term outcomes are particularly poorly covered.